The Relationship Between Emotional intelligence and Digital Leadership of school Administrators Under Chiang Mai Secondary Education Service Area Office - Thummakun, Warunee; Buacharoen, Parichat; Somsathan, Prapatsorn (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were 1) to study the emotional intelligence level of school administrators under the Chiang Mai Secondary Educational Service Area Office, 2) to study the digital leadership of school administrators under the Chiang Mai Secondary Educational Service Area Office, and 3) to study the relationship between emotional intelligence and digital leadership of school administrators under the Chiang Mai Secondary Educational Service Area Office. The sample group of this research consisted of 87 school administrators under the Chiang Mai Secondary Educational Service Area Office. The instrument used in this research was a questionnaire 6 levels. The Data analysis using frequency distribution, percentage, mean, standard deviation and simple correlation coefficient. The results of the research were as follows: 1) the emotional intelligence of school administrators of school administrators under the Chiang Mai Secondary Educational Service Area Office over all and classified by aspect found that it was at true. 2) the digital leadership of school administrators of school administrators under the Chiang Mai Secondary Educational Service Area Office overall and classified by aspect was at quite true. 3) the relationship between emotional intelligence and digital leadership of school administrators under the Chiang Mai Secondary Educational Service Area Office was found that the correlation was quite high.